Analisis Wacana Dalam Percakapan Negosiasi Jual Beli Di Media Sosial Zona Vespa Sebagai Rekomendasi Materi Ajar Teks Negosiasi SMA Kelas X - Hamzah, Muhammad; Musa, Safuri; Pratiwi, Wienike Dinar (Peneliti.net, 2024)
Today's phenomena can be seen from the rapid progress of technology and information. With social media, of course it can be used as a place to socialize and interact with each other. Social media that are now widely used by the general public are Instagram and WhatsApp. This study aims to analyze discourse in buying and selling negotiations on social media in the Vespa zone based on superstructure or schematic theory according to van dijk in Eriyanto (2015) and utilize the results of discourse analysis as recommendations for teaching materials for class X high school negotiating texts. The benefits of this research are as recommendations for comparison between the structure of negotiating texts based on textbooks and conversations on social media and can be used as recommendations for ex-negotiation high school class X teaching materials. This study uses a descriptive qualitative method with a superstructure or schematic approach according to van Dijk's theory in Eriyanto (2015). The data source used is documentation of screenshots of conversations on the Vespa zone social media. The method of collecting data in this study are (1) documentation by way of screenshots of sales and purchase negotiation conversations on the Vespa zone social media, (2) using library techniques by looking for references to relevant journals and research The results of this study become recommendations for teaching materials in learning Negotiations Text in Senior High Schools. Teaching materials are packaged with computer-based multimedia and interactive videos.